The funerary use of caves during the Holocene in the Atlantic Western Pyrenees: New information from Atxuri-I and Txotxinkoba caves (Biscay, Northern Iberian Peninsula). (20th November 2020) - García-Sagastibelza, Andrea; López-Onaindia, Diego; Lambacher, Nicole; Pomeroy, Emma; Cubas, Miriam; Subirà, Maria Eulàlia; Castex, Dominique; Couture-Veschambre, Christine; Gómez-Olivencia, Asier
Abstract: The Atlantic Western Pyrenean area is exceptionally rich in archaeological evidence of funerary contexts dated to Late Prehistory. These funerary deposits are mainly recorded in caves and megalithic structures. Burials attributed to the Holocene have been recorded in more than 187 caves (177 just in Gipuzkoa and Bizkaia), reflecting the relevance of this phenomenon in the AWP. Nonetheless, just a few of these inhumation contexts have been properly studied, and even fewer have direct and systematic 14 C dates. Here, we present the results from the analysis of two sepulchral caves from Biscay: Atxuri-I and Txotxinkoba, that preserve a minimum number of 9 and 14 individuals, respectively. Both caves present subadult individuals of different ages-at-death and among adults, both sexes are represented. Although the representation of osteological elements is roughly similar in both sites, small differences in the preservation of pelvic bones and the completeness of long bones suggest a potential bias in Atxuri-I. We provide six new radiocarbon dates on human remains. Two 14 C dates from Atxuri-I show that the cave was used for funerary purposes at least during two very different times: the Mesolithic and the Bronze Age. The latter period is represented by a directly dated complete femur, which was also studied biomechanically, providing results similar with the available Bronze Age female sample from the Iberian Peninsula. The four dates from Txotxinkoba show that the cave was only used for a relatively short period during the Chalcolithic. When put within the Atlantic Western Pyrenean context, despite the limited amount of direct dates a pattern is evident, where most of the largest accumulations of human remains are found in sites with Chalcolithic burials (between 4, 600 and 4, 000 BP), such as Lacilla II, Pico Ramos, Urtao II and Abauntz, and Txotxinkoba would fit within this group. Those caves that show human burial chronologies spanning longer periods of time, such as Lumentxa, Santimamiñe, Marizulo or Aizpea, generally contain smaller numbers of individuals, and Atxuri-I would fit within this group.